Electrospun poly(ɛ-caprolactone)/collagen scaffolds with potential use for skin regeneration - Lizarazo-Fonseca, Liliana; Muñoz Prieto, Efrén; Vera Graziano, R; Camacho, Bernardo; Salguero, Gustavo; Silva Cote, Ingrid (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Current treatments for skin lesions repair are autografts, allografts and biosynthetic dermal substitutes. However, only autograft therapy gives best results, but it is subject to skin area affected in burned patient, other treatments only give temporary coverage to wound, evidencing need to generate structures that besides protecting wound have biological functions that contribute to the repair or regeneration of the skin. In order to generate a dressing that meets these characteristics, poly (ℇ-caprolactone) / collagen type I scaffolds were fabricated by electrospinning to be evaluated as possible dermal substitutes. These scaffolds were characterized by SEM, contact angle, ATR-FTIR, TGA, DSC and their biocompatibility were evaluated by adhesion and proliferation of Wharton’s Jelly mesenchymal stromal cells (WJ-MSC). It was found that collagen presence in scaffolds decreases fiber diameter and improves hydrophilicity favoring adhesion of WJ-MSC. It was found that the presence of collagen in the scaffolds decreases the fiber diameter and improves the hydrophilicity favoring the adhesion processes of the CEM-GW. In addition, it was shown that it is not necessary to use high amounts of collagen to obtain a scaffold with favorable physicochemical and biological characteristics.